2019
DOI: 10.1186/s12864-019-5808-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of bolting in A. tequilana reveals roles for florigen, MADS, fructans and gibberellins

Abstract: Background Reliable indicators for the onset of flowering are not available for most perennial monocarpic species, representing a drawback for crops such as bamboo, agave and banana. The ability to predict and control the transition to the reproductive stage in A. tequilana would represent an advantage for field management of agaves for tequila production and for the development of a laboratory model for agave species. Results Consistent morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 45 publications
2
36
0
1
Order By: Relevance
“…Transcriptome analysis of the vegetative to reproductive transition in A. tequilana revealed no differential expression for starch metabolism related genes (Zavala- Garcia et al, 2018) whereas fructan related genes are highly expressed in SAM tissue in comparison to leaf tissue. In particular a 6G-FFT isoform is specifically and strongly expressed at the initial stage of the reproductive phase (Avila De Dios et al, 2019).…”
Section: Agave Fructansmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome analysis of the vegetative to reproductive transition in A. tequilana revealed no differential expression for starch metabolism related genes (Zavala- Garcia et al, 2018) whereas fructan related genes are highly expressed in SAM tissue in comparison to leaf tissue. In particular a 6G-FFT isoform is specifically and strongly expressed at the initial stage of the reproductive phase (Avila De Dios et al, 2019).…”
Section: Agave Fructansmentioning
confidence: 99%
“…Delgado Sandoval et al, 2012, showed that as the reproductive stage initiates, development of photosynthetically active leaves is suppressed and the SAM differentiates. Genes encoding FEH and invertases increase their expression during bolting (Avila De Dios et al, 2019) and leaves and stems senesce indicating that carbohydrate reserves are being harnessed for flowering.…”
Section: Biological Functions Of Agave Fructansmentioning
confidence: 99%
“…16,73 At present, there is scarce information on the genomic organization of the Agave genus, and also a few transcriptome and proteomic analyses of Agave species, which makes it difficult to identify putative protein-coding genes that respond to drought, heat stress, and flowering. [73][74][75] It is hoped that future studies will identify essential genetic and biochemical mechanisms beneficial to biotechnology geared toward engineering drought-and disease-tolerant C 3 and C 4 plants, and even interspecies agaves of interest. 76 Nevertheless, in silico analyses have already identified potential cellulase synthases, glucanases, and sucrose synthases that could be utilized in fiber production.…”
Section: Agave Drought Tolerance and Synthetic Biologymentioning
confidence: 99%
“…Two-year RNA-seq analysis in different tissue -For the estimation of tissue-specific expression, we consulted the assembled transcriptomic library, obtained by Illumina sequencing, in different tissues and the stages of development of A. tequilana, by Ávila de Dios at the Simpson CIN-VESTAV-Irapuato Laboratory. Extraction, preparation, and TSA library assembly are described in detail by (De Dios et al 2019).…”
Section: Analysis Of the Amino Acid And Structural Sequence Of Thementioning
confidence: 99%